Communication Skills In English Among Telugu Medium Students In Secondary Schools Of Visakhapatnam District (Journal of Namibian Studies : History Politics Culture, 2023)
The present study has been designed to investigate the Communication Skills in English among Telugu medium students in the Secondary  Schools of Visakhapatnam District. Various Indian and foreign studies were reviewed. Descriptive Survey  method  has been used in this study. The study was conducted over a sample of 200 (boys and girls) secondary school students in Visakhapatnam district using stratified random sampling method. Questionnaire was constructed for the secondary school students to find out the opinions of students on Communication Skills in English among Telugu medium students in Secondary Schools of Visakhapatnam District. The data were analyzed using various statistical methods like mean, SD, t-test and ANOVA by SPSS package. The results revealed that, there is a significant difference between the perceptions of students according to their gender, class, school management, locality and parental qualification towards Communication Skills in English among Telugu  medium students in Secondary Schools of Visakhapatnam District. The results are discussed in light of previous research studied; suggestions and Recommendations for further research were also suggested.